Effect of Fermentation Time of Kombucha Tea on Its Hypoglycaemic Activity in Rats - Nur A. Setiani; Rika L. Anggriani; Anggi Restiasari (Universitas Padjadjaran, Indonesia)
Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycaemia. Functional food, such as kombucha tea, is widely used as complementary treatment for type 2 diabetes mellitus. Kombucha tea is made through fermentation process of green or black tea using a microbial kombucha consortium (Acetobacter xylinum and several types of yeast). The aim of this study was to evaluate the effect of fermentation time of kombucha tea on its hypoglycaemic activity in rats. The green tea (Camellia sinensis) was fermented with kombucha consortium for 8, 14, and 21 days. Evaluation of hypoglycaemic activity was conducted using glucose tolerance test method. First, fasting blood glucose levels in rats were measured after 16 hours fasting. Hyperglycaemic condition was induced by administering glucose 2 g/0.2 kg body weight. Blood glucose levels were measured again after 30 minutes. Subsequently, 5.5 ml of kombucha tea in various fermentation time was orally administered. Blood glucose levels were measured at 30, 60, 90, 120, 150 and 180 minutes after kombucha tea administration. The results revealed the average reduction of blood glucose were 18.16%, 33.64%, and 19.88% by kombucha tea fermented for 8, 14, and 21 days, respectively. In conclusion, kombucha tea fermented for 14 days is potential to be developed as a hypoglycaemic agent. Keywords: fermentation time, glucose level, hypoglycaemia, kombucha tea